Peran ALKI II dalam Mendukung Keamanan Ibu Kota Nusantara: Tinjauan Strategis dan Pertahanan - Himawan, Yudha (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
ALKI II (Indonesian Archipelago Sea Lane II) is a strategic sea lane connecting the Indian Ocean with the South China Sea and is very important in supporting the security and stability of the newly built Indonesian Capital City (IKN) in East Kalimantan. However, this region faces various challenges such as illegal maritime activities, limited surveillance technology, and geopolitical dynamics due to foreign military activities. The purpose of this study is to analyze the role of ALKI II in supporting the security of the Indonesian Capital City by identifying the challenges and opportunities in the region. This study uses a qualitative method, with a descriptive analytical approach to relevant secondary data. Based on the results of the study, it was found that although ALKI II faces threats in the form of piracy, smuggling, illegal fishing, and geopolitical influence, opportunities for international cooperation through joint military exercises and improvements in surveillance technology offer significant solutions. In addition, environmental problems such as marine pollution and ecosystem degradation also affect security stability in this region. In conclusion, strengthening international cooperation, modernizing defense technology, and strict environmental policies are key to ensuring that ALKI II can effectively support the security of the Indonesian Capital City.